Oral Leukoplakia Related to Malignant Transformation - Teruo Amagasa; Masashi Yamashiro; Hitoshi Ishikawa (2006)
Abstract Oral leukoplakia and its malignant transformation are reviewed in this article. Oral leukoplakia is defined as a predominantly white lesion of the oral mucosa that can not be characterized as any other definable lesion; however, the lesion must be confirmed histopathologically by biopsy in order to discuss malignant transformation of oral leukoplakia. Malignant transformation rates of oral leukoplakia range from 0.13 to 17.5%, while the rates of five‐year cumulative malignant transformation range from 1.2 to 14.5%. Some reports found a high incidence of malignant transformation in older patients. Chewing tobacco and smoking are distinct risk factors particularly among males in certain countries; however, other countries have noted that females or non‐smokers may be at risk of malignant transformation. HPV has been detected in oral dysplasia lesions and cancer in non‐smokers. Conflicting reports have been presented regarding the malignant transformation of oral leukoplakia with epithelial dysplasia; however, we and some authors believe that epithelial dysplasia is an important factor in the malignant transformation of oral leukoplakia. The majority of researchers showed non‐homogenous leukoplakia as a risk factor, although different terms have been used to describe these lesions. There may be several routes to malignant transformation of oral leukoplakia, including transformations induced by carcinogenesis due to betel quid chewing or smoking, or by HPV infection. While no definite treatment modalities for oral leukoplakia have been established, we suggest surgical therapy with an adequate safety‐margin and well‐timed evaluation as an appropriate treatment in preventing malignant transformation.